Antenatal and neonatal antecedents of learning limitations in 10-year old children born extremely preterm. (March 2018) - Leviton, Alan; Joseph, Robert M.; Allred, Elizabeth N.; O'Shea, T. Michael; Kuban, Karl K.C.
Abstract: Background: Children born extremely preterm are at increased risk of learning limitations. Aim: To identify the antecedents of learning limitations of children born extremely preterm. Study design: Prospective observational study from birth to age 10 years. Variables entered into the multinomial logistic regression analyses were ordered temporally, with the earliest occurring predictors/covariates of each learning limitation risk entered first and not displaced by later occurring covariates. Subjects: 874 children who were born before the 28th week of gestation. Outcome measures: A reading limitation was defined as a score one or more standard deviations below the expected mean on the WIAT-III Word Reading and a mathematics limitation was defined as a similarly low score on the Numerical Operations component. Results: 56 children had a "reading ONLY" limitation, 132 children had a "math ONLY" limitation and 89 children had "reading AND math" limitations. All risk profiles included an indicator of socioeconomic disadvantage ( e . g ., mother's "racial" identity and eligibility for government-provided health care insurance), an indicator of newborn's immaturity/vulnerability ( e . g ., high illness severity score, receipt of hydrocortisone, and/or ventilator-dependence at 36 weeks post-menstruation), and all but the math only limitation included an indicator of fetal growth restriction and inflammation ( i . e ., pregnancy urinary tract infection or late ventilator-dependence). Conclusions: The themes of socioeconomic disadvantage and immaturity/vulnerability characterize all three risk profiles, while the themes of fetal growth restriction and inflammation are characteristic of a reading limitation only, and the reading and math limitations entity. Highlights: Among 10-year old children born extremely preterm, the risk profiles of a 'reading ONLY' limitation, a 'math ONLY' limitation, and the combination of 'reading AND math' have similarities and differences. All risk profiles included an indicator of socioeconomic disadvantage and an indicator of newborn's immaturity/vulnerability. An indicator of fetal growth restriction and inflammation were characteristic of the risk profiles of a reading ONLY limitation, and the reading AND math limitations entity. These findings provide support for the hypothesis that what applies to children born at term also applies to children born extremely preterm The higher risks of learning limitations in children born extremely preterm than among children born at term probably reflect the increased frequency of immaturity/vulnerability and its consequences including heightened risk neonatal inflammatory processes.